Highly rapid-response electrical heaters based on polymer-infiltrated carbon nanotube networks for battery thermal management at subzero temperatures. (5th January 2023) - Wang, Zhi-Xing; Du, Pei-Yao; Li, Wen-Jing; Meng, Jin-Hao; Zhao, Li-Hua; Jia, Shen-Li; Jia, Li-Chuan
Abstract: Conductive polymer composites (CPCs) of high filler loads hold great promise as rapid-response electrical heaters for battery thermal management at subzero temperatures. However, it is still a huge challenge to achieve high filler loads in CPCs due to the processing difficulties. Herein, we demonstrated the fabrication of highly conductive CPCs embedded with high filler loads based on polymer-infiltrated carbon nanotube (CNT) networks through the facile brush-coating and thermal treatment methods. The unique polymer-infiltrated CNT networks enabled the composites with outstanding electrical conductivity (2082.0 S/m) and excellent Joule heating performance (a high steady-state temperature of 70.4 °C at a low supplied voltage of 2.5 V). Moreover, the composites exhibited excellent Joule heating behavior at subzero temperatures, and it took only 31 s for the battery to reach 0 °C when the composites were applied to preheat the battery at −20 °C. It is believed that this work offers an efficient strategy for the versatile design of highly conductive CPCs as rapid-response electrical heaters and provides insights on the development of highly efficient technique for battery thermal management at subzero temperatures. Graphical abstract: Image 1